Equations balanced on the previous day | Equations balanced on the next day |
Mg(NO3)2 + 2 KOH = Mg(OH)2 + 2 KNO3
Mn + KNO3 + KOH = KNO2 + K2MnO4 + H2O =>
Mn + 3 KNO3 + 2 KOH = 3 KNO2 + K2MnO4 + H2O
Fe(NO3)3 = Fe{+3} + NO3{-} =>
Fe(NO3)3 = Fe{+3} + 3 NO3{-}
AlCl3 + Ba(OH)2 = BaCl2 + Al(OH)3 =>
2 AlCl3 + 3 Ba(OH)2 = 3 BaCl2 + 2 Al(OH)3
AgNO3 + (NH4)2CO3 = Ag2CO3 + NO3NH4 =>
2 AgNO3 + (NH4)2CO3 = Ag2CO3 + 2 NO3NH4
Na2S + NaSH + O2 = Na2S2O3 + NaOH =>
Na2S + NaSH + 2 O2 = Na2S2O3 + NaOH
NiCO3 + HBF4 + H2O = [Ni(H2O)6][BF4]2 + CO2 =>
NiCO3 + 2 HBF4 + 5 H2O = [Ni(H2O)6][BF4]2 + CO2
NaHSO4 + Zn = Na2SO4 + ZnSO4 + H2 =>
2 NaHSO4 + Zn = Na2SO4 + ZnSO4 + H2
Cu + HNO3(conc) = Cu(NO3)2 + NO + H2O =>
3 Cu + 8 HNO3(conc) = 3 Cu(NO3)2 + 2 NO + 4 H2O
Fe(NO3)3 = Fe{+3} + NO3{-} =>
Fe(NO3)3 = Fe{+3} + 3 NO3{-}
Mn{2+} + ClO3{-} + H2O = MnO2 + Cl{-} + H3O{+} =>
3 Mn{2+} + ClO3{-} + 9 H2O = 3 MnO2 + Cl{-} + 6 H3O{+}
HNO2 + NH3 = NH4 + NO2 =>
HNO2 + NH3 = NH4 + NO2
Fe(NO3)3 = Fe{+3} + NO3{-} =>
Fe(NO3)3 = Fe{+3} + 3 NO3{-}
MgSO4 + NH3 = Mg3N2 + H2SO4 =>
3 MgSO4 + 2 NH3 = Mg3N2 + 3 H2SO4
K2SO4 + Ba(NO3)2 = BaSO4 + (KNO3)2 =>
K2SO4 + Ba(NO3)2 = BaSO4 + (KNO3)2
C2H6 + I2 = C2H5I + HI =>
C2H6 + I2 = C2H5I + HI
Br2 + OH{-} = BrO3 + Br{-} + H2O =>
7 Br2 + 12 OH{-} = 2 BrO3 + 12 Br{-} + 6 H2O
Fe(NO3)3 = Fe{+3} + NO3{-} =>
Fe(NO3)3 = Fe{+3} + 3 NO3{-}
Zn(OH)2 + CO2 = Zn(CO3) + H2O =>
Zn(OH)2 + CO2 = Zn(CO3) + H2O
CaCO3 + MgO = Mg(CO3) + CaO =>
CaCO3 + MgO = Mg(CO3) + CaO
Fe2O3 + CO = Fe + CO2 =>
Fe2O3 + 3 CO = 2 Fe + 3 CO2
H(NO3) + Na(OH) = Na(NO3) + HOH =>
H(NO3) + Na(OH) = Na(NO3) + HOH
Cu2SO6 + HNO3 = Cu(NO3)2 + H2SO4 + NO4 + H2O =>
3 Cu2SO6 + 14 HNO3 = 6 Cu(NO3)2 + 3 H2SO4 + 2 NO4 + 4 H2O
NaNO2 + H2SO4 = NaNO3 + SO2 + H2O =>
NaNO2 + H2SO4 = NaNO3 + SO2 + H2O
C2H5OH + O2 = CO2 + H2O =>
C2H5OH + 3 O2 = 2 CO2 + 3 H2O
NH3CuCl2 = Cu(NH3)Cl2 =>
NH3CuCl2 = Cu(NH3)Cl2
C5H10 + KMnO4 + H2SO4 = C5H10O2 + K2SO4 + MnSO4 + H2O =>
5 C5H10 + 4 KMnO4 + 6 H2SO4 = 5 C5H10O2 + 2 K2SO4 + 4 MnSO4 + 6 H2O
NaNO3 + H2O = NaOH + HNO3 =>
NaNO3 + H2O = NaOH + HNO3
S + N2 = S3N2 =>
3 S + N2 = S3N2